2015
DOI: 10.3329/bjmed.v25i2.25087
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Primary Glomerulonephritis in Dhaka Medical College Hospital, Bangladesh

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…Other findings with low incidence of IgM nephropathy and pauciimmune GN matches with other studies 10,13 like in Pakistanwhere the incidence of IgM nephropathy was 2.47%. 38 Most of the studies did not mention IgM nephropathy as a distinct category.…”
Section: Primary Gnsupporting
confidence: 78%
See 4 more Smart Citations
“…Other findings with low incidence of IgM nephropathy and pauciimmune GN matches with other studies 10,13 like in Pakistanwhere the incidence of IgM nephropathy was 2.47%. 38 Most of the studies did not mention IgM nephropathy as a distinct category.…”
Section: Primary Gnsupporting
confidence: 78%
“…Mundi I et al 10 found most of the cases were in 21-40 age range and distinct pattern of PGN was found in different age ranges. The age range of our cases was 14-72 years with a slight male predominance (1.2:1) except in case of LN and MesPGN.…”
Section: Clinical Profilementioning
confidence: 99%
See 3 more Smart Citations